Manajemen Pengembangan Karakter pada Lembaga Pendidikan Islam: Character Development Management in Islamic Education Institutions - Abdurahman, Abdurahman; Rahman, Diana; Badrudin, Badrudin (STAI Publisistik Thawalib Jakarta, 2024)
Islamic education plays a significant role in shaping the character of students through effective management to integrate character development into the learning process. The study aims to examine character-based management in Islamic educational institutions. This research employs a qualitative method with a literature study approach. Data were collected from scientific journals and books. The results show: (1) management is a series of planned actions from planning to evaluation. (2) character development is the process of combining values or components into something. (3) Islamic educational institutions are schools based on Islamic religion to shape religious students. (4) character development management in Islamic educational institutions is a framework for organizing and managing education, considering Islamic character development such as honesty, justice, and patience in the curriculum and classroom learning. Conclusion: character development management is able to shape students to become more Islamic in schools.